AUTOCLAVE FOR MODERN BUILDING MATERIALS WORKING IN THE METHOD (American Journal of Business Management, Economics and Banking, 2023)
For the fast and high-quality production of modern construction materials, it is necessary to use different heat treatment devices for various structural elements, because they are required to serve for a long time without losing their strength under the influence of external forces. The article presents calculations on the methods of heat treatment of building materials by the autoclave method.